Motivasi Belajar Siswa terhadap Mata Pelajaran Pendidikan Agama Islam di SDN Mandalawangi - Siti Nurazizah; Enoh; Asep Dudi Suhardini (UNISBA Press, 2022)
Abstract. Islamic religious education is very important for students because, in the process of self-development and growth, students need guidance, direction, and teaching of Islamic education. In this way, students' learning motivation must be applied and improved in this subject, because in carrying out learning activities, participants must be based on having learning motivation. Therefore, to increase learning motivation, it is necessary to know and understand the factors that influence students' learning motivation to achieve the expected learning objectives. Learning motivation will move someone to do learning activities. However, entering the era of the Covid-19 pandemic the learning process was carried out boldly after the impact of the students. Based on these conditions, researchers are interested in being able to explain